Heat Adaptive Capacity: What Causes the Differences Between Residents of Xiamen Island and Other Areas? - Wu, Chaowei; Shui, Wei; Yang, Haifeng; Ma, Meiqi; Zhu, Sufeng; Liu, Yuanmeng; Li, Hui; Wu, Furong; Wu, Kexin; Sun, Xiang (Frontiers in Public Health, 2022)
Extreme heat events caused by climate change have serious adverse effects on residents’ health in many coastal metropolises in southeast China. Adaptive capacity (AC) is crucial to reducing heat vulnerability in the human-environment system. However, it is unclear whether changes in individual characteristics and socioeconomic conditions likely amplify or attenuate the impacts of residents’ heat adaptive capacity (HAC) changes. Moreover, which public policies can be implemented by the authorities to improve the HAC of vulnerable groups remains unknown. We conducted a questionnaire survey of 630 residents of Xiamen, a typical coastal metropolis, in 2018. The effects of individual and household characteristics, and government actions on the residents’ HAC were examined by using ordinal logistic regression analysis. Results show that the majority (48.10%) of Xiamen residents had a “medium” HAC level, followed by a “high” level (37.14%). On Xiamen Island, residents who settled locally for one–three years and spent less than one hour outdoors might report weaker HAC, and their HAC would not improve with increased air conditioning units in household. In other areas of Xiamen, residents with more rooms in their households, no educational experience, and building areas less than 50 square meters might report better HAC. Further, vulnerable groups, such as local residents and outdoor workers on Xiamen Island, people lacking educational experience and renters in other areas of Xiamen, showed better AC to hot weather than those in previous studies. Low-income groups should be given more attention by local governments and community groups as monthly household income played a positive role in improving Xiamen residents’ HAC. Rational green spaces planning and cooling services, such as street sprinkling operations, provided by municipal departments can effectively bring benefits to Xiamen residents. Identification of basic conditions of AC has significant implications for practical promoting targeted measures or policies to reduce health damages and livelihood losses of urban residents during extreme heat events.